Introducing a New Broad-based Index of Financial Development - Svirydzenka, Katsiaryna (Washington, D.C. : International Monetary Fund, 2016)
There is a vast body of literature estimating the impact of financial development on economic growth, inequality, and economic stability. A typical empirical study approximates financial development with either one of two measures of financial depth - the ratio of private credit to GDP or stock market capitalization to GDP. However, these indicators do not take into account the complex multidimensional nature of financial development. The contribution of this paper is to create nine indices that summarize how developed financial institutions and financial markets are in terms of their depth, access, and efficiency. These indices are then aggregated into an overall index of financial development. With the coverage of 183 countries on annual frequency between 1980 and 2013, the database should offer a useful analytical tool for researchers and policy makers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet